Analysis of the market of physical culture and health services in Lviv - Приступа, Євген; Жданова, Ольга; Чеховська, Любов (Slobozhanskyi Herald of Science and Sport, 2017)
Yevhen Prystupa, Olha Zhdanova & Liubov Chekhovska Today, fitness services are in demand among the Ukrainian population. The saturation of the market for fitness clubs in large and small cities is different. Purpose: to study the market of physical culture and health services in Lviv. Material & Methods: theoretical analysis and generalization of scientific literature, sources and information of the world Internet, comparison method, documentary method. Results: in the article the analysis of the market of the establishments that provide physical culture and health services in Lviv is presented. Fitness club "FitCurves" provides services only to women, but the fitness club "Olympus" is the only one that offers Crossfit services. "Clubs Malibu", "Kiwi fitness" have schools for the training of group coaches. Social responsibility is one of the most important principles of the network "Sport Life". Conclusion: conditions for ensuring the content and active leisure of the population of Lviv are provided: 78 fitness clubs, 16 swimming pools, 64 sports clubs, 6 tennis courts, 10 stadiums, etc. All establishments offer a wide range of fitness services. Price policy of season tickets for fitness clubs is different.